Solidarity as an Ethical Action - Głos, Aleksandra (Studia Polityczne, 2018)
Solidarity is one of the most popular concepts in social philosophy, and one of the vaguest. Controversially, theses on its final decline and on its emerging new forms are being posed simultaneously. In response, this article describes the most important challenges to the theory of solidarity and proposes a new definition of it, based on contemporary social and political philosophy. Solidarity, because of the constituent role of values in uniting solidary associations, and because of its special ethos, can be described as a form of ethical cooperation stemming from recognition and trust, and leading to radical mutual responsibility.